2003
DOI: 10.1159/000072069
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Examinations of Stratum corneum Lipid Models Exposed to Ultraviolet Irradiation

Abstract: Lipid model systems consisting of the major components of the stratum corneum intercellular lipid matrix were studied to investigate the ultraviolet-radiation-mediated damage of these biomolecules. Pure lipids and liposomes were irradiated using a lamp emitting a solar radiation spectrum. The influences of the irradiation and the effects of added iron ions were studied by electrospray ionization mass spectrometry (MS) with an ion trap analyser. Exact mass measurements were carried out using a time-of-flight ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…We interpret this effect to be due to special conditions. The beneficial influence of additional antioxidants like ·-tocopherol is often discussed [25]. However, in our study, ascorbic acid itself, in the absence of ·-tocopherol, demonstrated a placebo-controlled antioxidant potential.…”
Section: Discussioncontrasting
confidence: 59%
“…We interpret this effect to be due to special conditions. The beneficial influence of additional antioxidants like ·-tocopherol is often discussed [25]. However, in our study, ascorbic acid itself, in the absence of ·-tocopherol, demonstrated a placebo-controlled antioxidant potential.…”
Section: Discussioncontrasting
confidence: 59%
“…To characterize differences in lipidomes among biological samples of interest, the relative intensities or areas given from mass spectrometers are only helpful as semi-quantitative values ( 11,12 ). Precise quantitative values of lipidomes of interest would also be desirable, especially in the case of evaluations of lipid dynamics in de MS has been employed for the analysis of CERs in human SC as follows: reversed-phase LC (RPLC)-ESI-MS ( 22,(30)(31)(32); ESI-MS ( 33,34 ); RPLC-thermospray-MS ( 35 ); and NPLC-APCI-MS (36)(37)(38)(39). However, those methods were not validated as quantitative methods for overall CER species in the SC, although some studies reported quantitative values based on unrealistic assumptions.…”
mentioning
confidence: 99%
“…Peaks at m/z 317, 299, 281 and 263 are also present in the spectrum due to the amine carbon chain fragment which undergoes three successive dehydrations as observed by Trommer et al. (23) for the phytosphingosine structure. No peaks were observed at higher molar masses, due to either the formation of new oxygenated molecules or to rearrangements.…”
mentioning
confidence: 55%